An Examination of Students’ Critical Thinking Skills in the Context of the Digestive System - Safitri, Tiffany; Kurniasih, Surti; Rachman, Indriyani; Yayoi, Kodama (Jurnal Inovasi Pendidikan IPA, 2025)
Critical thinking is vital in education, helping students analyze and evaluate information for better decision-making. However, research on fostering critical thinking in science education remains limited, particularly in topics like the digestive system. The digestive system topic is conceptually rich and closely related to students' daily lives, making it a suitable context to assess critical thinking. This study aims to reveal the essential thinking profiles of junior high school students in Bogor City on the topic of the digestive system, focusing on Ennis’s indicators. A quantitative method was employed, involving 108 students who completed an essay test with five open-ended questions assessing critical thinking across five indicators: providing simple explanations, building basic support, making inferences, offering further explanations, and setting strategies. Participants were selected using purposive sampling, targeting students who had completed the digestive system topic. Semi-structured interviews with three science teachers supplemented the findings. The findings indicated that students demonstrated very low critical thinking abilities, with the lowest scores in providing further explanations (22.83%) and the highest in setting strategies (43.58%) among 108 junior high school students in Bogor. Based on teacher interviews, the current instructional approach predominantly employs lecture-based and textbook-oriented methods, which emphasize factual recall over critical analysis. This traditional approach significantly contributes to students' low performance in essential indicators of thinking. The study offers valuable insights into the challenges and opportunities for fostering critical thinking in science education, highlighting the importance of targeted interventions to address specific deficiencies